The development of Assessment of SpondyloArthritis international Society classification criteria for axial spondyloarthritis (part II): validation and final selection - Rudwaleit, M.; van der Heijde, D.; Landewe, R.; Listing, J.; Akkoc, N.; Brandt, J.; Sieper, J. (Bmj Publishing Group, 2009)
Objective: To validate and refine two sets of candidate criteria for the classification/diagnosis of axial spondyloarthritis (SpA). Methods: All assessment of SpondyloArthritis international Society (ASAS) members were invited to include consecutively new patients with chronic (>= 3 months) back pain of unknown origin that began before 45 years of age. The candidate criteria were first tested in the entire cohort of 649 patients from 25 centres, and then refined in a random selection of 40% of cases and thereafter validated in the remaining 60%. Results: Upon diagnostic work-up, axial SpA was diagnosed in 60.2% of the cohort. Of these, 70% did not fulfil modified New York criteria and, therefore, were classified as having non-radiographic'' axial SpA. Refinement of the candidate criteria resulted in new ASAS classification criteria that are defined as: the presence of sacroiliitis by radiography or by magnetic resonance imaging (MRI) plus at least one SpA feature (imaging arm'') or the presence of HLA-B27 plus at least two SpA features (clinical arm''). The sensitivity and specificity of the entire set of the new criteria were 82.9% and 84.4%, and for the imaging arm alone 66.2% and 97.3%, respectively. The specificity of the new criteria was much better than that of the European Spondylarthropathy Study Group criteria modified for MRI (sensitivity 85.1%, specificity 65.1%) and slightly better than that of the modified Amor criteria (sensitivity 82.9, specificity 77.5%). Conclusion: The new ASAS classification criteria for axial SpA can reliably classify patients for clinical studies and may help rheumatologists in clinical practice in diagnosing axial SpA in those with chronic back pain.
Keywords: Inflammatory Back-Pain; Ankylosing-Spondylitis; Diagnostic-Criteria; Rheumatic-Diseases; Clinical History; Sacroiliitis; Spondylarthropathy; Efficacy